Microsatellite Marker for Genetic Variation Analysis in Local Chili Pepper (Capsicum frutescens L.) Induced by Ethyl Methane Sulfonate (EMS) - Ria Reinnata Juliandari; Retno Mastuti; Estri Laras Arumningtyas (Journal of Tropical Life Science, 2019)
Mutation using Ethyl Methane Sulfonate (EMS) is a simple and quick method to produce genetic variation in chili pepper. In this study, a total of 3 genotypes of local chili pepper (Capsicum frutescens L.), i.e. Genotype 2 (G2), Genotype 7 (G7), and Genotype 11 (G11) were induced by EMS with concentrations of 0% (K0), 0.01% (K1), 0.02% (K2), and 0.04% (K3). Genetic variation analysis in mutant was performed based on 3 microsatellite markers CA 19, CA 27, CA 62. Those molecular markers successfully detected the genetic variation in chili pepper mutant based on the number and size of microsatellite alleles variation. The 3 genotypes of chili pepper mutant produced a total of 15 alleles with the average Polymorphism Information Content (PIC) value of 0.82. Compared to the control plant, genetic variations in genome level were observed in local chili pepper. Furthermore, the treatment of EMS with concentration of 0.04% produced the most notable genetic variation in 3 genotypes of local chili pepper.Â